Language Use In Lok Baintan Floating Market of Banjar District of South Kalimantan - Fatchul Muin (Universitas Muhammadiyah Sidoarjo, 2019)
Through this paper, the author describes the following: (1) Languages ​​used in Lok Baintan Floating Market, (2) Language behaviors of sellers in Lok Baintan Floating Market, (3) Typical linguistic elements used in Lok Baitan Floating Market, and (4) Linguistic characteristics that characterize culture in the environment of Lok Baintan Floating Market. From the description of the language usage, the conclusions that can be asked are as follows: Languages ​​and language activities at the Lok Baintan Floating Market Location in this simple research are examined through linguistic perspectives, and it is continued by relating socio-cultural aspects. Thus, the use of the language is also examined in the anthropology of language. Based on the results of data analysis, it was concluded that there is a mutual relationship between language and culture. In certain perspectives, language is one of the seven elements of culture, and in other perspectives culture and its all aspects involve language to accommodate that culture. Banjarese language has accomodated Banjarese culture. The use of Banjarese Language in the domain of buying and selling at Lok Baintan Floating Market is a reflection of Banjarese Culture. Banjarese culture is a code of conduct, including language behavior. Banjarese culture is reflected in the Banjar Language. Banjarese culture is manifested in the speech event in which Banjarese language is used for communication.